Monografia: Clasificación histopatológica de tumores mamarios en caninos. (2021)
The mammary gland is in charge of nourishing by producing milk / colostrum to neonatals until tooth development to be able to ingest solid food and transmit passive immunity from the mother to her young to protect them from disease (Cunnigham, 2013). The characterization of a malignant neoplasm is based on evading suppressor genes growth, resist cell death, allow replicated immortality, induce angiogenesis, activation of invasion and metastasis, maintain proliferative signaling, genome instability and mutation, inflammation as a growth promoter, dysregulate cellular energy, avoid immune destruction (Yi Chen Et al., 2021). Although there are factors that predispose the appearance of tumors in the mammary gland, there are also protective effects such as ovary hysterectomy at an early age that decreases as the estrus pass and the protection disappears if the surgery has not been performed before the fourth estrus or at two and a half years (Sanchez C, 2014)